Traditional Farmers of Wamena Tribes in Jayapura-Indonesia - Marthen Timisela; Daniel D Kameo; Neil Samuel Rupidara; Roberth Siahainenia (Jurnal Manajemen Hutan Tropika, 2020)
Traditional agriculture has a relationship with the culture of the local community that is the norms agreed upon by the ancestors related to the use of natural resources to meet the needs of daily life. This article aims to describe the traditional agricultural process of the Wamena people in Jayapura, Indonesia. The perspective used in analyzing traditional agricultural processes was the perspective of sustainable livelihoods of traditional communities in a development context. This research was done in a descriptive-qualitative manner by using primary and secondary data. The primary data was obtained from in-depth interviews. Meanwhile, the secondary data was obtained from observations and document studies. The results indicate that the traditional agricultural process of the Wamena Tribe in Jayapura was able to maintain the livelihoods of traditional communities based on the principles of sustainable development. This could be seen from several stages, such as access to land resources, land ownership, agrarian social relations, and gender issues in the division of traditional agricultural work of the Wamena people in Jayapura. This shows that the local wisdom in the cultural norms of the Wamena people could be used in environmentally friendly agricultural activities that did not have a conflict with the perspective of sustainable development.